Teaching practices in the management of medications at the emergency unit - Carneiro, Taize Muritiba; Silva, Iranete Almeida Sousa (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objective: to relate the experience of the authors in the creation and implementation process of a theoretical-practical activity related to the management of medications. Methodology: this is a descriptive study, an experience report, developed during the supervised internship for Nursing in Emergencies from the School of Nursing at a University in the city of Salvador, Bahia, Brazil. The proposed model was divided in three phases: delivery of the medications list to be examined; daily practical activities during care to patients; and group discussion about prescription deadlines for a clinical case study. Results: the methodology developed for the teaching-learning process, allowed for the construction of knowledge based on reflection practices and on conscious and ethical attitudes in regards to the administration of medications by future nurses. Conclusion: this experience allowed for a closer look at the reality of the day-to-day of the nurse in reference to deadlines, management, and supervision of medications, as well as legal and ethical implications. Descriptors: nursing; medication errors; education in nursing; emergency nursing; patient care; medication systems; hospital; nursing care. RESUMO Objetivo: apresentar a experiência das autoras na criação e implementação de uma atividade teórico-prática sobre administração de medicamentos. Metodologia: estudo descritivo do tipo relato de experiência desenvolvido durante o estágio supervisionado da disciplina Enfermagem em Emergências da faculdade de enfermagem de uma Universidade da cidade de Salvador, Bahia, Brasil. O modelo proposto foi dividido em três momentos: entrega de lista de medicamentos para estudo, atividade prática diária durante a assistência ao paciente e discussão em grupo para aprazamento da prescrição de medicamentos em um estudo de caso clínico. Resultados: o método desenvolvido para o processo de ensino-aprendizagem possibilitou a construção de conhecimento fundamentado na prática reflexiva e numa atitude consciente e ética para a administração de medicamentos pelos futuros enfermeiros. Conclusões: a experiência favoreceu uma aproximação com a realidade do cotidiano do enfermeiro no que se refere aos cuidados com o aprazamento, a supervisão e a administração de medicamentos bem como suas implicações ético-legais. Descritores: enfermagem; erros de medicação; educação em enfermagem; enfermagem em emergência; assistência ao paciente; sistemas de medicação no hospital; cuidados de enfermagem. RESUMEN Objetivo: presentar la experiencia de las autoras en la creación e implementación de una actividad teórica-práctica sobre la administración de medicinas. Metodología: estudio descriptivo de tipo relato de experiencia desarrollado durante la práctica profesional supervisionada de la disciplina Enfermería en Emergencias de la faculdad de efermería de una Universidad de la ciudad de Salvador, Bahia, Brasil. El modelo propuesto fue dividido en tres momentos: entrega de la lista de medicinas para estudio, actividad práctica diária durante la asistencia al paciente y discusión en grupo para el aplazamiento de la prescripción de medicinas en un estudio de caso clínico. Resultados: El método desarrollado para el proceso de enseñanza-aprendizaje posibilitó la construcción de conocimiento fundamentado en la práctica reflexiva y en una actitud consciente y ética para la administración de medicinas por los futuros enfermeros. Conclusiones: la experiencia favoreció una aproximación con la realidad del cotidiano del enfermero en lo que se refiere a los cuidados con el aplazamiento, la supervisión y la administración de medicinas, así como, sus implicaciones éticolegales. Descriptores: enfermería; erros de medicación; educación en enfermería; enfermería de urgência; atención al paciente; sistemas de medicación en hospital; atención de enfermería.